Farmer perceptions of the COVID-19 pandemic’s impact on agriculture: A case study from Madura Island, Indonesia - Eko Setiawan; Setiani Setiani; Wen-Chi Huang (Agriekonomika, 2022)
The worldwide COVID-19 epidemic has had a great impact on farming and socioeconomic institutions all over the globe.This study aims to understand farmer knowledge and perceptions of the impacts of the one-year COVID-19 pandemic on agricultural systems. We purposefully picked 400 farmers from four regencies in Madura Island, Indonesia. The survey was administered from April to August 2021. Maize, rice, peanuts, tobacco, cassava, and chili peppers are the five most cultivated plants, while chicken and cattle are the main livestock raised. Farmers’ perceptions, measured on a 5-point Likert scale (from 1—not affected, to 5—severely affected), showed that COVID-19 had an average minor to moderate effect (average score of 2.49±0.9) on the agriculture system. The greatest impact is on farm income (average scale of 3.76±0.79), while the ability to plant crops in the upcoming season is the lowest (average scale of 1.2±0.56).